Governing the UK - Peele, Gillian (Blackwell, 1995)
This well-established textbook develops a framework for understanding the radical changes in the relationships between the polity, economy and society which have occurred across the last two decades. This new edition brings to the fore the impact on British government and politics, of Europe, factors of social change, the decline of consensus, the shaping of a more marked ideological politics and the rising tide of technology. Against the backdrop of her analytical framework, Peelse sets out the details of the British system of Government providing students with a clear understanding of the basic machinery of Government and the Constitution - Executive, Legislature and the Judiciary - as as well as of the forces shaping the dynamics of political change such as parties, voting behaviour and pressure groups.